Fruitful Clinical Results of L- Arginine Supplementation in Illnesses of Various Etiologies (Medical Forum Monthly, 2021)
Objective: To evaluate pros and cons of L-Arginine supplementation as protective adjuvant against lithium hepatitis in rats.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at the Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre, Karachi, Sindh from October 2012 to March 2013.Materials and Methods: Sixty adult rats were selected and divided into four groups A, B, C and D with further division into three Subgroups based on periods of treatment 2, 6 and 12 weeks respectively. A was control group, B was on lithium, C was on both lithium and Arginine and group D was on Arginine alone. The initial and final body and absolute and relative liver weights of rats were recorded after scarification at the end of each treatment period. Livers were cut into 3um thick sections stained with hematoxylin and eosin for histological & morphometrical examinationResults: The findings in groups A and D were normal while in group B animals body and liver weights were increased with morphological changes. Group C animals exhibited significant changes in body and liver weights in comparison with B animals with least inflammation and morphological changes due to L-Arginine co-administration with lithiumConclusion: It is suggested that lithium induced hepatic-toxicity could be attenuated with L-Arginine.